Prescribing Pattern of Antibiotics Utilization in Surgery, Pediatric, and General Medicine Wards in a Tertiary Care Hospital, Bengaluru, India - Azimifard, Nader (Asian Journal of Pharmaceutics (AJP), 2019)
Objective: To prescription pattern of antibiotic drugs in different medical facilities such as general medicine, surgery, and pediatrics, in a tertiary care hospital and evaluate the antibiotics utilization pattern and check the adherence to the antibiotic policy to explore reasons for the non-adherence. Materials and Methods: A total of 300 inpatients were included in this study. Prescriptions and treatment chart of inpatients were reviewed prospectively for prescribed patterns of proton pump antibiotics. The inpatient case sheets and prescriptions will be screened for analysis of prescriptions for various effects of antibiotics on a daily basis. All the prescribed medications along with other medications and relevant information will be noted in a customized data collection form to find out the antibiotics utilization. The antibiotic prescription will be assessed whether it is according to hospital antibiotic policy and in case of violation, the reason for it will be noted down. The incidence and cause for the nosocomial infection will be noted down. The incidence and cause for the nosocomial infection were noted down. Results: In our study, it is found that out of 300 patients 60.5% were male and 39.5% were females, and thus the average number of drugs per patient was 7. Among studied patients, 3.67% were using 1–3 medication followed by 27.14% of patients using 4–6 medications. According to extensive (70%) antibiotics were observed in the study population. In our study, patients suffering from GIT ailments, appendicitis, pancreas, pulmonary, central nervous system, cardiovascular system, bone, liver genitourinary problems, fever, and suffering from dengue. In our study, various class of antibiotics such as penicillin’s, macrolides, cephalosporin’s, and fluoroquinolones were prescribed. There were various combination drugs prescribed which are specific to the disease out of which ampicillin+gentamicin+metronidazole (5%) and ampicillin + gentamicin + cefotaxime + aminoglycoside (5%). Conclusion: Most common antibiotic used was ceftriaxone, more than one antibiotic was prescribed, and only 11% of antibiotics were prescribed in the generic name. Most common antibiotic used was ceftriaxone. Number of antibiotics prescribed per prescription was 1.83. Antibiotics was mostly prescribed by brand name. The concluded the adherence to hospital policy in prescribing antibiotics was largely seen. In appropriate use of antibiotics is detected due to lack of culture sensitivity test which has to make mandatory in the hospital before antibiotic prescription. In our study, Polypharmacy was seen in a large extent were patients were put on 4–5 antibiotics ,which also has to be avoided by using broad spectrum antibiotics and fixed dose antibiotics suitably.